Relationship between learning styles and academic achievement among UiTM Students' Athlete SUKIPT 2018 / Nurulain Remli - Remli, Nurulain (2018)
The purpose of the study is to identify and determine the relationship between learning styles and academic achievement among students. This research was applied quantitative study which will use questionnaire. A total of 200 UiTM students' athlete that participates in SUKIPT 2018 has been selected. The questionnaires were divided into two sections which was section A - Demographic data, section B - learning styles. The sampling that used was purposive sampling. The Statistical Package for Social Science version 23 (SPSS 23) will be used to analyse and interpret the data to generate descriptive frequencies. The Chi-Square was used to analyse the relationship and Independent t-Test to investigate the relationship.